Pengaruh Kualitas Pelayanan, Harga dan Pomosi Terhadap Keputusan Pembelian Susu Milk UHT PT. Sayap Utama Mas - Rizal Bakti; Wahjuny Djamaa; Garbada Boris Setyawan; Agustini Agustini; Rio Eldianson; Willy Saputra (Departement of Mathematics Education, 2024)
Competition between milk distributor companies has become very tight, so each milk distributor company needs to have a special strategy to deal with competition. Business as it is today requires a marketing concept that is right on target to achieve success for the company. Marketers are expected to meet customer needs, are required to provide quality services that have advantages for their customers, set prices, and promote products and services effectively. Companies must work hard to create new strategic policies in selling their products and services in the face of fierce competition with competitors who can provide greater value to customers. This study was conducted to determine the Influence of Service Quality, Price and Promotion on the Purchase Decision of Milka UHT 200 mL Milk at PT. Main Gold Wing (Case Study on Wholesaler in DC. Mampang). The type of research conducted using a quantitative approach with the research method used is survey research using questionnaires as a basic data collection tool. The data analysis model used is multiple linear regression analysis. To determine the sample to be used, researchers use incidental sampling techniques. Hypothesis test results .1). Partially, the quality of service has a significant effect on the purchase decision of Milku UHT Milk. 2). Partially, the price has a significant effect on the purchase decision of Milku UHT Milk 200 mL 3). Partially, the promotion does not have a significant effect on the purchase decision of Milku UHT 200 mL Milk